Slogan Back to the al-Quran and Sunnah: Studi atas Gerakan Politik Islam Jamaluddin al-Afghani - Syahuri Arsyi (Prodi Tata Negara (Siyasah) IAIN Langsa, 2020)
This article will discuses the Islamic political movements of one the thinker renewal of Islamic modernism in the 19th century, namely is Jamaluddin al-Afghani (1839-1897). This study used historical approach, to understand and explore one's personality by looking at this socio-culture and intellectual background to social impression. This study found, first the political movement’sal-Afghani is very unique and different than another. Her movement to carried out in the frame of slogan “back to the al-Quran and the Sunnah” as response to the attitude of Muslims that are experiencing deterioration and decline, and a response to western imperialism in the Islamic world. al-Afghanito encourage of Muslims to united in the pan-Islamism. Second, al-Afghani uses the slogan “back to the al-Quran and the Sunnah” in his political movement as well as a spirit for the Muslims to re-ijtihad-sasi against, especially to the concepts of qada’ and qadar which are often misunderstood untill result in Muslims are trapped in an attitude of fatalism and static.